2017
DOI: 10.1590/1678-457x.22716
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dendrobium officinale polysaccharide on adipogenic differentiation of rat bone marrow mesenchymal stem cells

Abstract: This study investigated the effect of Dendrobium officinale polysaccharide (DDP) on the adipogenic differentiation of rat bone marrow mesenchymal stem cells (BMSCs). DDP was extracted fresh Dendrobium officinale. Rat BMSCs were prepared, and then were treated with 0 (control), 50, 100, 200, 400, 800 μg/mL DDP, respectively. The cell viability was determined by MTT assay. The adipogenic differentiation was quantitatively analyzed by oil red D staining assay. The mRNA expressions of adipogenic differentiation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Subsequently, 90% (v/v) ethanol was used to elute the resin and dissolve the adsorbed flavanone in ethanol. The AJWTF extract was ultimately obtained by steam-drying ethanol [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, 90% (v/v) ethanol was used to elute the resin and dissolve the adsorbed flavanone in ethanol. The AJWTF extract was ultimately obtained by steam-drying ethanol [14].…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, 0.01 g of AJWTF extract was dissolved in 5 mL of 90% ethanol, and 2 mL of AJWTF extract solution was poured into a 25-mL volumetric flask. The flavonoid content in the AJWTF extract was determined using the repeated rutin standard curve method (rutin meter) [14].…”
Section: Methodsmentioning
confidence: 99%
“…23 Moreover, ZHAO et al revealed that DOP has a great role in regulating cell fate of BMSCs. 24 It could inhibit adipogenic differentiation in Rat BMSCs by deregulating adipogenesis-related gene expression of PPARγ, LPL and FABP4. 24 However, the role of DOP in age-related bone loss and lineage commitment of BMSCs is still unclear.…”
mentioning
confidence: 99%
“…Nowadays, it is popular to extract the biological products from the plants and microorganism, which have been used in the protection of plants or human beings, due to the natural friendliness (Dai et al, 2017;Dong et al, 2014;Zhao et al, 2017). Prodigiosin is a critical bioactive compound with common applications in the food, pharmaceutical, cosmetic and textile industries.…”
Section: Introductionmentioning
confidence: 99%